The effect of oral use of concentrated pomegranate juice by mothers on hyperbilirubinemia in neonates under phototherapy: A randomized clinical trial - Masomeh Rezapour; Yadollah Zahedpasha; Mohammad Kamalinejad; Zahra Memariani; Morteza Alijanpour; Mousa Ahmadpour-Kacho; Seyyed Ali Mozaffarpur; Hoda Shirafkan (Journal of Research in Medical Sciences, 2023)
Background: Hyperbilirubinemia is a common problem in neonates that causes hospitalization. The aim of this study was to investigate the effects of concentrated pomegranate juice (CPJ) consumption by breastfeeding mothers on neonatal hyperbilirubinemia. Materials and Methods: In this open-labeled, add-on, randomized clinical trial, 86 breastfeeding mothers and their neonates were allocated into two groups. In the control group, neonates received phototherapy. Besides neonates' phototherapy in the intervention group, their mothers received CPJ (1 tablespoon [15 g] three times a day) up to discharge. The bilirubin level was the primary outcome. The duration of phototherapy, the duration of hospital stay, and the need for exchange transfusions were secondary outcomes. Results: CPJ reduced the bilirubin level of hospitalized neonates within 48 h after consumption (P = 0.048, standard mean difference = 0.648). It also resulted in reduced duration of hospital stay and faster discharge of the neonates. Furthermore, in 48 h after discharge, bilirubin was significantly lower in the CPJ group (P = 0.003, partial eta squared = 0.123). Conclusion: Compared to the control group, consumption of CPJ by lactating mothers whose infants underwent phototherapy resulted in lower bilirubin levels, shorter hospital stay, and faster discharge.